Cross-Market Causal Linkages of ASEAN-5 - Evan, Lau; Swee-Ling, Oh (IUP Publications, 2009)
This study seeks to understand the nature of international stock markets and the extent to which the ASEAN-5 markets causally relate with each other before and after the 1997-98 turmoil. The data series of the Composite Index (CI) in logarithm form and the volatility series of GARCH were adopted for this study. The econometric approach of Toda and Yamamoto (1995) disclosed separate findings for both the series. Generally, markets deemed to be more causally related in the post-crisis period, than prior to it. Conclusively, lesser opportunities for international portfolio diversification were made available within the regional scope as markets possess long-run predictability measures.